Local Community Initiatives in Riau Peat Villages - Berliana Yufani; M Rawa El Amady (AAI Pengda Riau, 2024)
This study recorded the local community initiatives in five-peat villages in Riau Province as a community adaptation effort to changes in the peat ecosystem. This study is a qualitative study conducted from January to April 2020. The data is presented and analysed descriptively. This study reports that the communities in the five-peat villages are very dynamic and able to adapt well to the zero-burn farming policy. The community took the initiative to change the types of plants and develop forestry and non-forest service businesses. The farming ecosystem has been formed in the village's studio with pineapple varieties, kelulut honey, and village tourism. The parties need to support these local community initiatives based on a partnership ecosystem.